The thermal properties and thermoelectric performance of γ-graphyne nanoribbons. (3rd March 2016) - Yang, Zhi; Ji, Yu-Long; Lan, Guoqiang; Xu, Li-Chun; Wang, Hua; Liu, Xuguang; Xu, Bingshe
Abstract: The thermal properties and thermoelectric performance of one-dimensional armchair and zigzag γ -graphyne nanoribbons ( γ -GYNRs) are theoretically investigated in the present study. We found that the pristine γ -GYNRs hold lower phononic thermal conductance and better figure of merit ( ZT ) than graphene nanorribons. The maximal ZT values for the armchair and zigzag γ -GYNRs are 0.93 and 0.61, respectively. By introducing 14 C atoms, the thermoelectric conversion efficiencies of γ -GYNRs are greatly enhanced, thus the isotope effect can significantly improve the thermoelectric properties of the systems. More importantly, under a relatively low temperature, the maximal ZT of a defective zigzag γ -GYNR is as high as 2.12, indicating that γ -GYNRs are promising materials for constructing excellent thermoelectric nanodevices.